Cultural Route and Ecomuseum Concepts as a Synergy of Nature, Heritage and Community Oriented Sustainable Development Ecomuseum „Ibar Valley“ in Serbia - Terzić, Aleksandra; Bjeljac, Željko; Jovičić, Ana; Penjišević, Ivana (European Journal of Sustainable Development, 2014)
<!–[if gte mso 9]> <![endif]–> In tourism trends on global level became obvious the popularity of cultural tourism. There is a growing interest and connection between natural and cultural heritage with a living societies, with the growing concern for nature and heritage preservation. Importance of tourism and the role of cultural tourism are becoming of strategic importance in global economy, especially in underdeveloped countries. This study examine the successful management practices in creation of culture based tourism destinations and applying their practices to undeveloped regions. Study is using principles and practices that are in-line with “eco-museum”, “cultural routes” and “cultural district” ideals, which break from traditional approaches to heritage management and tourism use. The aim is to highlight the synergies between common philosophy and promotion, safeguarding and conservation of heritage and enhancing the economic, social and cultural well-being of local communities. Theoretical base of study is focused on principles of tourism valorization method applied on heritage complexes, sustainability indicators of tourism development and a survey conducted on a focus group of tourism experts engaged in Ibar Valley in Serbia, that enabled the quantitative results of the evaluation process. The aim is to highlight the synergies between landscape, heritage and festivals (living culture), trough safeguarding and conservation of heritage resources and tourism promotion. Keywords:culture, tourism, heritage, management, promotion <!–[if gte mso 9]> Normal 0 14 false false false IT X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>